Distinct roles of age and abdominal visceral fat in reducing androgen receptor‐dependent negative feedback on LH secretion in healthy men. (30th April 2014) - Takahashi, P. Y.; Liu, P. Y.; Veldhuis, J. D.
Summary Testosterone (T) impacts luteinizing hormone (LH) secretion through negative feedback via the androgen receptor (AR) in the hypothalamo‐pituitary system. An untested postulate is that increasing body mass index (BMI), abdominal visceral fat (AVF) or total abdominal fat (TAF) with ageing decreases LH secretion by heightening T negative feedback via AR. This hypothesis was tested in a prospective, randomized double‐blind cross‐over study of 19 healthy men comparing the effects of flutamide, a selective non‐steroidal AR antagonist and placebo administration on basal and pulsatile LH secretion as a function of age and obesity measures. To this end, serum levels of 2‐hydroxyflutamide (2‐OHF), a major active flutamide metabolite, were measured by mass spectrometry, and AVF/TAF quantified by abdominal computerized tomography. Statistical analysis showed that antiandrogen administration elevated 6‐h mean LH concentrations to 5.4 ± 1.3 IU/L compared with 3.3 ± 1.2 IU/L for placebo (p < 10−3), and total T by 35% (p < 10−4). The LH‐T concentration product doubled (p < 10−8). According to deconvolution analysis, flutamide exposure increased total LH secretion (p < 10−3) and pulsatile LH secretion (p = 0.0077), along with LH pulse frequency (p = 0.019). Despite feedback inhibition, the LH‐T product declined as a linear function of AVF (p = 0.021) and TAF (p = 0.017). This was explained by the fact that higher BMI was associated with lower 2‐OHF concentrations (R = −0.562, p = 0.012). In contrast, age was associated with less pulsatile LH secretion (R = −0.567, p = 0.011) even when LH responses were normalized to antiantrogen levels. In conclusion, increased AVF, TAF and BMI predict decreased LH and flutamide blood levels, whereas older age is marked by impaired stimulation of pulsatile LH secretion even when normalized for antiandrogen levels, suggesting different mechanisms of regulation by adiposity and age.